Adat Pernikahan Melayu Jambi: Konsep Patriarki dalam Tradisi Matrilineal di Desa Teluk Kuali, Kec. Tebo Ulu, Kab. Tebo - Elza Ramona (An-Nuha : Jurnal Kajian Islam, Pendidikan, Budaya dan Sosial, 2023)
This article aims to describe the dominance of men in Jambi Malay wedding customs in Teluk Kuali Village. In the kinship system, the people of Teluk Kuali have a tendency towards the matrilineal tradition, in which the lineage is based on the mother's line. In this study a qualitative-descriptive method was used with unstructured interview data collection techniques and conducting a search of the literature relating to Jambi Malay wedding customs and the like. Both in the form of books and journal articles. The results of this study indicate that in almost every Jambi Malay traditional wedding ceremony in Teluk Kuali Village, men dominate. The wedding rites of Teluk Kuali Village are mostly negotiations for decision making which are mostly attended by men. Even though the people of Teluk Kuali hold a matrilineal tradition, in practice women are not represented in every decision-making of traditional marriage rites. Women are indirectly marginalized from adat and from women themselves.